The tumor suppressor MIR139 is silenced by POLR2M to promote AML oncogenesis - Stavast, Christiaan J; van Zuijen, Iris; Karkoulia, Elena; Özçelik, Arman; van Hoven-Beijen, Antoinette; Leon, Leticia G; Voerman, Jane S A; Janssen, George M C; van Veelen, Peter A; Burocziova, Monika; Brouwer, Rutger W W; van IJcken, Wilfred F J; et al. (Leukemia, 2022)
MIR139 is a tumor suppressor and is commonly silenced in acute myeloid leukemia (AML). However, the tumor-suppressing activities of miR-139 and molecular mechanisms of MIR139-silencing remain largely unknown. Here, we studied the poorly prognostic MLL-AF9 fusion protein-expressing AML. We show that MLL-AF9 expression in hematopoietic precursors caused epigenetic silencing of MIR139, whereas overexpression of MIR139 inhibited in vitro and in vivo AML outgrowth. We identified novel miR-139 targets that mediate the tumor-suppressing activities of miR-139 in MLL-AF9 AML. We revealed that two enhancer regions control MIR139 expression and found that the polycomb repressive complex 2 (PRC2) downstream of MLL-AF9 epigenetically silenced MIR139 in AML. Finally, a genome-wide CRISPR-Cas9 knockout screen revealed RNA Polymerase 2 Subunit M (POLR2M) as a novel MIR139-regulatory factor. Our findings elucidate the molecular control of tumor suppressor MIR139 and reveal a role for POLR2M in the MIR139-silencing mechanism, downstream of MLL-AF9 and PRC2 in AML. In addition, we confirmed these findings in human AML cell lines with different oncogenic aberrations, suggesting that this is a more common oncogenic mechanism in AML. Our results may pave the way for new targeted therapy in AML.
Keywords: Animals; Myeloid-Lymphoid Leukemia Protein; Cell Line, Tumor; Mice, Knockout; myši knockoutované; fúzní onkogenní proteiny; nádorové buněčné linie; lidé; Oncogene Proteins, Fusion; Carcinogenesis; regulace genové exprese u leukemie; karcinogeneze; epigeneze genetická; RNA-polymerasa II; akutní myeloidní leukemie; mikro RNA; RNA Polymerase II; Gene Expression Regulation, Leukemic; MicroRNAs; zvířata; Mice, Inbred C57BL; Leukemia, Myeloid, Acute; Epigenesis, Genetic; protoonkogenní protein MLL; myši inbrední C57BL; Humans